2007
DOI: 10.1083/jcb.200611058
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan and CD44 antagonize mitogen-dependent cyclin D1 expression in mesenchymal cells

Abstract: High molecular weight (HMW) hyaluronan (HA) is widely distributed in the extracellular matrix, but its biological activities remain incompletely understood. We previously reported that HMW-HA binding to CD44 antagonizes mitogen-induced S-phase entry in vascular smooth muscle cells (SMCs; Cuff, C.A., D. Kothapalli, I. Azonobi, S. Chun, Y. Zhang, R. Belkin, C. Yeh, A. Secreto, R.K. Assoian, D.J. Rader, and E. Puré. 2001. J. Clin. Invest. 108:1031–1040); we now characterize the underlying molecular mechanism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 42 publications
5
67
3
Order By: Relevance
“…Sucrose gradient fractionation confirmed that chloroquine treatment induced a shift in the content of Hyal1WT-tdT (fractions 12-17 in Fig. 4G) to higher density fractions (fractions [13][14][15][16][17][18][19] as well as a small portion localized to the least dense fractions 4 and 6. Moreover, the lower molecular mass band decreased in intensity, consistent with reduced cleavage of Hyal1 as occurs in acidified vesicles.…”
Section: Inhibition Of Lysosomal Acidification Causes Buildup Of Hyal1mentioning
confidence: 86%
See 2 more Smart Citations
“…Sucrose gradient fractionation confirmed that chloroquine treatment induced a shift in the content of Hyal1WT-tdT (fractions 12-17 in Fig. 4G) to higher density fractions (fractions [13][14][15][16][17][18][19] as well as a small portion localized to the least dense fractions 4 and 6. Moreover, the lower molecular mass band decreased in intensity, consistent with reduced cleavage of Hyal1 as occurs in acidified vesicles.…”
Section: Inhibition Of Lysosomal Acidification Causes Buildup Of Hyal1mentioning
confidence: 86%
“…The Hyal1 band consistent with the intact secreted mass of Hyal1-tdT is ϳ100 kDa and can be observed to co-fractionate in all three cell lines with EEA1 (fractions 4 -6), cathepsin D (two bands; fractions 13-17), and calnexin (fractions [13][14][15][16][17][18][19], which correspond to fractions of early endosomes, lysosomes, and microsomes (ER), respectively. However, close comparison of the fractions reveals a greater portion of uncleaved enzyme species in the Hyal1E131Q-tdT cell line that specifically extends throughout the denser fractions (fractions 14 -19) of the sucrose gradient in contrast to the wild-type and Y202F mutant, which are more similar to the profile of cathepsin D fractions (fractions [13][14][15][16][17]. These results support an active role in vesicular trafficking by catalytically active Hyal1 cargo.…”
Section: Catalytically Active Hyal1 Is Found In Vesicular Compartmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we have shown that the widely expressed ECM component, hyaluronan (HA), acts as a negative regulator of G 1 phase by inhibiting the mitogen-dependent induction of cyclin D1. 12 HA also inhibits mitogen-dependent induction of Skp2 and degradation of p27, but epistasis experiments showed that the effects of HA on Skp2 and p27 are secondary to the inhibition of cyclin D1. 12 Inhibition of the Skp2 autoinduction loop can easily explain how an HA-mediated decrease in cyclin D1 levels would inhibit Skp2 expression and stabilize p27 through inhibition of Rb phosphorylation (Fig.…”
Section: Identification Of a Skp2 Autoinduction Loop That Regulates Pmentioning
confidence: 99%
“…CD44, a type 1 transmembrane receptor expressed on the surface of smooth muscle cells and platelets. CD44 exists in many different isoforms that all have HA binding properties [10] and regulate several signaling pathways including Src family kinases, Rho family GTPases, extracellular signal-regulated kinases and mitogen activated protein kinase (MAPK) [11,12] and thereby mediates both cell adhesion and cell growth [13,14].…”
Section: Introductionmentioning
confidence: 99%